2011
DOI: 10.1002/cctc.201000448
|View full text |Cite
|
Sign up to set email alerts
|

Amidases Have a Hydrogen Bond that Facilitates Nitrogen Inversion, but Esterases Have Not

Abstract: The fact that proteases/amidases can hydrolyze amides efficiently whereas esterases can not has been discussed during the last decades. By using molecular modeling we have found a hydrogen bond in the transition state for protease/amidase catalyzed hydrolysis of peptides and amides donated by the scissile NH‐group of the substrate. The hydrogen‐bond acceptor was found either in the enzyme (enzyme assisted) or in the substrate (substrate assisted). This new interaction with the NH‐hydrogen in the transition sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Left: Boosting promiscuous activity by focusing on the in silico discovery [23,24] and engineering [34] of key mechanistic structural elements in modern enzymes is represented by the forward gear. This is exemplified by focusing on a hydrogen bond acceptor (arrow) that could act as a shifter for enhanced amidase over esterase activity by facilitating nitrogen inversion (structure shown), a key step in amide bond hydrolysis [26]. We have shown that the previously unacknowledged key hydrogen bond donated by the reacting NH-group facilitates nitrogen inversion, the overall rate limiting step of enzyme catalyzed amide bond hydrolysis [26,27,35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Left: Boosting promiscuous activity by focusing on the in silico discovery [23,24] and engineering [34] of key mechanistic structural elements in modern enzymes is represented by the forward gear. This is exemplified by focusing on a hydrogen bond acceptor (arrow) that could act as a shifter for enhanced amidase over esterase activity by facilitating nitrogen inversion (structure shown), a key step in amide bond hydrolysis [26]. We have shown that the previously unacknowledged key hydrogen bond donated by the reacting NH-group facilitates nitrogen inversion, the overall rate limiting step of enzyme catalyzed amide bond hydrolysis [26,27,35].…”
Section: Resultsmentioning
confidence: 99%
“…This is because proteases and amidases, which cleave both esters and amides with high efficiency (relative activity 10 3 due to the resonance stabilization of amides [25]), capitalize on the additional hydrogen sitting on the reacting nitrogen atom of amide substrates. Amidases afford hydrogen bond formation to the reacting NH-group in the transition state (TS) [26], which results in efficient amidase activity ( Figure 1, left), regardless of protein fold, reaction mechanism, or topology of catalytic dyads/triads [27] displayed by amidases [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations